2014
DOI: 10.1007/s12264-014-1444-6
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule dynamics in axon guidance

Abstract: Precise modulation of the cytoskeleton is involved in a variety of cellular processes including cell division, migration, polarity, and adhesion. In developing post-mitotic neurons, extracellular guidance cues not only trigger signaling cascades that act at a distance to indirectly regulate microtubule distribution, and assembly and disassembly in the growth cone, but also directly modulate microtubule stability and dynamics through coupling of guidance receptors with microtubules to control growth-cone turnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 136 publications
(201 reference statements)
2
62
0
Order By: Relevance
“…Although our results indicate that UNC5C specifically interacts with TUBB3, not TUBB1 or TUBB2, it remains to be determined whether other UNC5 homologs, such as UNC5A, UNC5B, and UNC5D, can functionally associate with these ␤-tubulin isoforms in netrin-1-mediated repulsion. In response to netrin-1, UNC-5 coordinates with either DCC or DSCAM to initiate axon repulsion (Keino-Masu et al, 1996;Kolodziej et al, 1996;Leonardo et al, 1997;Hong et al, 1999;Finger et al, 2002;Purohit et al, 2012), whereas collaboration of DCC with DSCAM mediates chemoattraction (Ly et al, 2008;Liu et al, 2009;Qu et al, 2013b;Huang et al, 2015). Our recent studies suggest that DSCAM coordinates with DCC in coupling netrin-1 signaling to MT dynamics via dynamic TUBB3 to promote axon outgrowth, branching, and attraction (Qu et al, 2013a;Huang et al, 2015).…”
Section: Tubb3 Is a Key Downstream Component In Netrin-1 Signalingmentioning
confidence: 89%
See 2 more Smart Citations
“…Although our results indicate that UNC5C specifically interacts with TUBB3, not TUBB1 or TUBB2, it remains to be determined whether other UNC5 homologs, such as UNC5A, UNC5B, and UNC5D, can functionally associate with these ␤-tubulin isoforms in netrin-1-mediated repulsion. In response to netrin-1, UNC-5 coordinates with either DCC or DSCAM to initiate axon repulsion (Keino-Masu et al, 1996;Kolodziej et al, 1996;Leonardo et al, 1997;Hong et al, 1999;Finger et al, 2002;Purohit et al, 2012), whereas collaboration of DCC with DSCAM mediates chemoattraction (Ly et al, 2008;Liu et al, 2009;Qu et al, 2013b;Huang et al, 2015). Our recent studies suggest that DSCAM coordinates with DCC in coupling netrin-1 signaling to MT dynamics via dynamic TUBB3 to promote axon outgrowth, branching, and attraction (Qu et al, 2013a;Huang et al, 2015).…”
Section: Tubb3 Is a Key Downstream Component In Netrin-1 Signalingmentioning
confidence: 89%
“…For instance, dynamic MTs are preferentially oriented and stabilized in the direction of GC turn (Tanaka and Kirschner, 1995); local stabilization of MTs in one side of the GC is sufficient to cause the GC turn to that side (Buck and Zheng, 2002); stabilizing MTs and promoting their polymerization at plus ends increase axon outgrowth in vitro and in vivo (Sengottuvel et al, 2011); asymmetric redistribution of dynamic MTs toward the far side of the GC is involved in Wnt5a-promoted cortical axon outgrowth and repulsion (Li et al, 2014).…”
Section: Disengagement Of Unc5c With Polymerized Tubb3 In Netrin-1 Rementioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the dedicated regulators like BMP7 or Rac1 affect only the growth of either axons or dendrites, bimodal regulators like Sema3A execute binary functions that promote axon or dendrite growth while inhibiting the other [2] . Accompanying growth, differentiated axons exhibit guidance properties that Liu et al review in great detail [3] . A subject of interest for many years, axon guidance is crucial for neuronal function and the microtubule dynamics at the growth cone of axons has been considered as a classical paradigm for understanding cell motility and dynamics [3] .…”
mentioning
confidence: 99%
“…Accompanying growth, differentiated axons exhibit guidance properties that Liu et al review in great detail [3] . A subject of interest for many years, axon guidance is crucial for neuronal function and the microtubule dynamics at the growth cone of axons has been considered as a classical paradigm for understanding cell motility and dynamics [3] .In addition to neurons, a plethora of evidence has suggested that glia play pivotal roles during …”
mentioning
confidence: 99%